1993
DOI: 10.1254/jjp.61.267
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Inhibitory Effects of Calcium Antagonists on Cytosolic Ca2+ Levels Increased by High-Potassium or Glutamate in Cultured Rat Cerebellar Granule Cells

Abstract: ABSTRACT-Theanti-allergic and anti-inflammatory activities of DS-4574, which possesses leukotriene antagonism and inhibits the release of immunologically stimulated mediators such as histamine and leukotrienes, were evaluated in several animal models. DS-4574 had dose-dependent inhibitory effects on IgE-mediated passive cutaneous anaphylaxis and the passive Arthus reaction in rats and the phase I response of Forssman antibody-induced bronchoconstriction.In contrast, this compound had no effect on the phase II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…DS-4574 {6-(2-cyclohexylethyl)- [ 1,3,4] thiadiazolo [3,2-a ]-1,2,3-triazoloE4,5-d]pyrimidin-9(3H)-one} is a synthesized compound which was found to possess both mast cellstabilizing and peptidoleukotriene-antagonistic activities [1][2][3][4][5]. Previously we found that DS-4574 prevented experimental gastric lesions in rats [6,7] and inhibited basal gastric acid secretion in pylorus-ligated rats [6].…”
Section: Introductionmentioning
confidence: 99%
“…DS-4574 {6-(2-cyclohexylethyl)- [ 1,3,4] thiadiazolo [3,2-a ]-1,2,3-triazoloE4,5-d]pyrimidin-9(3H)-one} is a synthesized compound which was found to possess both mast cellstabilizing and peptidoleukotriene-antagonistic activities [1][2][3][4][5]. Previously we found that DS-4574 prevented experimental gastric lesions in rats [6,7] and inhibited basal gastric acid secretion in pylorus-ligated rats [6].…”
Section: Introductionmentioning
confidence: 99%